Clinical prediction models - Ranstam, J; Cook, J; Collins, G (Wiley, 2016)
Clinical prediction models (also known as prognostic models, risk scores) are mathematical equations that relate multiple predictors (risk factors, co-variates) to the probability of having a disease or condition (diagnostic) or the probability that an event will happen in the future (prognostic).